2015
DOI: 10.3390/su8010011
|View full text |Cite
|
Sign up to set email alerts
|

A Life Cycle Assessment of Silica Sand: Comparing the Beneficiation Processes

Abstract: Silica sand or quartz sand is a mineral resource with a wide variety of application; glass industry, construction and foundry are the most common examples thereof. The Republic of Croatia has reserves of 40 million tons of silica sand and a long tradition of surface mining and processing. The average annual production of raw silica sand in Croatia in the period from 2006 to 2011 amounted to 150 thousand tons. This paper presents cradle to gate LCA results of three different types of beneficiation techniques: e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…More complex processing methods cause polluting chemical emissions due to the use of fuels and reagents. Environmental impacts are caused by consumption of fossil fuels, electricity, water, and chemicals, with the major contributor shown to be fossil fuel use (Grbeš, 2016). Similar conclusions can be found in Ferreira and Leite (2015), who conducted an LCA of iron ore mining and concluded that fossil fuel consumption accounted for 36% of the total impact.…”
Section: Life Cycle Assessmentsupporting
confidence: 56%
See 1 more Smart Citation
“…More complex processing methods cause polluting chemical emissions due to the use of fuels and reagents. Environmental impacts are caused by consumption of fossil fuels, electricity, water, and chemicals, with the major contributor shown to be fossil fuel use (Grbeš, 2016). Similar conclusions can be found in Ferreira and Leite (2015), who conducted an LCA of iron ore mining and concluded that fossil fuel consumption accounted for 36% of the total impact.…”
Section: Life Cycle Assessmentsupporting
confidence: 56%
“…Kuzmanić T., Mikoš M.: Quartz Sand Use in Hydraulic and Sanitary Engineering -Kremenov pesek v hidrotehniki in komunali Acta hydrotechnica 33/58 (2020), 13-28, Ljubljana Grbeš (2016) conducted an LCA of three types of methods used for quartz sand mineral processing, namely electrostatic separation, flotation, and gravity concentration. Basic processing procedures (washing and sizing) showed the smallest impact, but those are insufficient for high-grade sand.…”
Section: Life Cycle Assessmentmentioning
confidence: 99%
“…For example, the recycling of green and amber glass bottles is generally limited to regions with extensive brewing and wine-making industries. Container glass recycling rates in Europe, USA and Australia are reported to be 73%, 34% and 42%, respectively, with significant diversity among the various regions, states and territories (Heriyanto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The production of container glass is an energy-intensive process with a substantial environmental impact (Mishra, 2015;Grbeš, 2016). Currently, the minimum energy consumption for container glass produced from 50% recycled cullet using the most efficient furnaces is estimated to be 3.85 MJ kg -1 (Conradt, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation